2002
DOI: 10.2343/geochemj.36.341
|View full text |Cite
|
Sign up to set email alerts
|

A noble gas study of the Kobe (CK4) chondrite by a stepwise heating method.

Abstract: We have investigated elemental and isotopic compositions of noble gases in the Kobe (CK4) chondrite by a stepwise heating method. The previously observed inconsistency in cosmic-ray exposure ages derived from cosmogenic 21 Ne and 38 Ar was eliminated in this study, and the averaged value of 38.2 Ma was obtained. Based on neutron-produced 80 Kr, a pre-atmospheric size of Kobe is estimated to be larger thañ 23 cm radius, whereas the results from cosmogenic radionuclides indicate a pre-atmospheric radius of 10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…They report the concordant cosmic-ray exposure ages obtained from spallogenic 21 Ne, 38 Ar and 83 Kr. The 21 Ne-based exposure age is 42 Ma, which is in agreement with that obtained by Matsumoto et al (2002). They also report a K-Ar age of 3.3 Ga. From the observed neutron-induced 80 Kr,82 Kr and 128 Xe, they suggest that the Kr isotopes were produced by epithermal neutron captures on 79 Br and 81 Br.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…They report the concordant cosmic-ray exposure ages obtained from spallogenic 21 Ne, 38 Ar and 83 Kr. The 21 Ne-based exposure age is 42 Ma, which is in agreement with that obtained by Matsumoto et al (2002). They also report a K-Ar age of 3.3 Ga. From the observed neutron-induced 80 Kr,82 Kr and 128 Xe, they suggest that the Kr isotopes were produced by epithermal neutron captures on 79 Br and 81 Br.…”
supporting
confidence: 79%
“…Results of noble gas analyses and petrological examinations of the meteorite were reported by Matsumoto et al (2001) and Tomeoka et al (2001), respectively. The 7 papers included in this special issue for the Kobe meteorite include reports on chemical compositions by Oura et al (2002) and Hirota et al (2002), petrology and mineralogy by Tachibana et al (2002), gammaray measurements for cosmic-ray induced radionuclides by Komura et al (2002), noble gas analyses by Matsumoto et al (2002) and Takaoka et al (2002), and X-ray computed tomography (CT) results for discussion of the nondestructive digital curation of meteorite samples by Tsuchiyama et al (2002). Oura et al (2002) employed neutron-induced prompt gamma-ray analysis (PGA) to analyze several lumps of sample of the Kobe meteorite, as well as a powdered sample and separated chondrules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of our study suggest that the estimation of higher equilibration temperatures for Kobe than for petrologic type 4 can be ascribed to shock induced heating at the state where the meteorite underwent thermal metamorphism. Matsumoto et al (2002) studied isotopic compositions of noble gases in Kobe and found that the release pattern of primordial noble gases is consistent with that the meteorite went through a shock event at an elevated temperature.…”
Section: Vesicular Olivine and Plagioclasementioning
confidence: 99%
“…The elemental and isotopic compositions of noble gases of the Towada meteorite are tabulated in Tables 2(a) Matsumoto et al, 2002;Takaoka et al, 2002;Eugster et al, 1993) as the end member isotopic ratios, where suffixes "c" and "t" mean cosmogenic and trapped components, respectively. Measured 20 Ne/ 22 Ne of 0.8132 is in the range of cosmogenic Ne, indicating negligible amount of trapped Ne in this meteorite.…”
Section: Noble Gas Resultsmentioning
confidence: 99%